2013
DOI: 10.1037/a0032448
|View full text |Cite
|
Sign up to set email alerts
|

Using electronic portfolios to foster literacy and self-regulated learning skills in elementary students.

Abstract: The research presented here is a continuation of a line of inquiry that explores the impacts of an electronic portfolio software called ePEARL. which is a knowledge tool designed to support the key phases of self-regulated learning (SRL)-forethought, performance, and self-reñecdon-and promote student learning. Participants in this study were 21 teachers from elementary schools (Grades 4-6) and their students (N = 319) from 9 urban and rural English school boards in Quehec and Alberta, Canada, who participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 52 publications
2
37
0
Order By: Relevance
“…To reach such a level, we recommend providing good access to technology, gaining support and recognition from school administrators, and providing training and support for teachers involved. A follow-up study by Abrami et al (2013) demonstrated that these conditions can lead to such a high level of implementation.…”
Section: Curriculum Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reach such a level, we recommend providing good access to technology, gaining support and recognition from school administrators, and providing training and support for teachers involved. A follow-up study by Abrami et al (2013) demonstrated that these conditions can lead to such a high level of implementation.…”
Section: Curriculum Factorsmentioning
confidence: 99%
“…In the Abrami et al (2013) study, students with low levels of enthusiasm scored significantly lower than students with high levels of enthusiasm on the student learning strategies questionnaire (SLSQ) (Abrami & Aslan, 2007). In the Chang et al (2013) study, students who were not satisfied with the e-portfolio scored significantly lower than their peers who were satisfied on several SDL measures in the portfolio, including selfjudgment.…”
Section: Personal Factorsmentioning
confidence: 99%
“…If the technology is thoughtfully and meaningfully used, or used for an authentic purpose, it may enhance the interest of students (Abrami, Venkatesh, Meyer, & Wade, 2013;Gunter, 2012;Jacobs, 2012). Jacobs (2012) also cautions that students may not necessarily come to class technology-literate.…”
Section: Key Definitionsmentioning
confidence: 99%
“…The portfolios can be used to store multiple student created artifacts (text, video, sound and images) and allow space for written dialogue among teachers, students, and parents for reflection, analysis and ranking of the pieces (Abrami et al, 2013(Abrami et al, , p. 1189.…”
Section: Technology and Reading Motivationmentioning
confidence: 99%
See 1 more Smart Citation